Improved probiotic survival to in vitro gastrointestinal stress in a mousse containing Lactobacillus acidophilus La-5 microencapsulated with inulin by spray drying. (January 2019) - Xavier dos Santos, Douglas; Casazza, Alessandro Alberto; Aliakbarian, Bahar; Bedani, Raquel; Saad, Susana Marta Isay; Perego, Patrizia
Abstract: This study aimed to optimize the spray drying process for the microencapsulation of Lactobacillus acidophilus La-5, using inulin as coating agent to increase its gastrointestinal survival. Moreover, the survival of the microencapsulated and the free microorganism incorporated or not in a synbiotic mousse to in vitro simulated gastrointestinal conditions was evaluated. Microencapsulation process conditions were optimized at 80 mL/min, 82%, and 10%, for feed flow, aspiration rate, and inulin concentration, respectively. Subsequently, a synbiotic diet mousse was produced with the addition both of the free and of the microencapsulated probiotic strain, and microorganism in vitro gastrointestinal resistance was evaluated. The lowest reduction of cell counts, after 6 h of the in vitro assays, occurred for mousse with microencapsulated cells (1.3 log cycles), followed by microencapsulated cells (2.0 log cycles), mousse with free cells (3.0 log cycles), and free cells (7.4 log cycles). Therefore, the spray drying process was appropriate to encapsulate the probiotic strain evaluated using inulin as coating agent and providing resistance to the microencapsulated microorganism. Moreover, the protection given by the microencapsulation process tested was further increased by the food product. Highlights: The effect of La-5 microencapsulation using inulin as coating agent was assessed. Microencapsulated La-5 had higher survival after spray drying process. The tested coating agent protected La-5 against artificial gastrointestinal juices. Encapsulated La-5 added in mousse had an excellent survival to simulated GI stress.